2020
DOI: 10.3390/microorganisms8071038
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Metschnikowia in Enology

Abstract: Over the last decade, several non-Saccharomyces species have been used as an alternative yeast for producing wines with sensorial properties that are distinctive in comparison to those produced using only Saccharomyces cerevisiae as the classical inoculum. Among the non-Saccharomyces wine yeasts, Metschnikowia is one of the most investigated genera due to its widespread occurrence and its impact in winemaking, and it has been found in grapevine phyllospheres, fruit flies, grapes, and wine fermentations as bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 80 publications
(197 reference statements)
4
49
0
Order By: Relevance
“…In 2020, shell-isolated nanoparticle-enhanced Raman spectroscopy was successfully applied for characterization of pulcherrimin [ 34 ]. Advances in genus Metschnikowia have been illustrated in two recent publications [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, shell-isolated nanoparticle-enhanced Raman spectroscopy was successfully applied for characterization of pulcherrimin [ 34 ]. Advances in genus Metschnikowia have been illustrated in two recent publications [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Z. bisporus is closely related to Z. bailii and Z. pseudobailii [ 83 , 84 ]. It was described as spoilage yeast with intermediate features between Z. rouxii and Z. bailii [ 71 , 72 ] and has been isolated from both healthy grapes [ 54 ] and rotten grapes [ 85 ]. From one of the bottled Essence wines, only Z. lentus was isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the genome sequences of certain strains of the pulcherrima clade revealed that their rDNA is fragmented and thus evolves via the birth-and-death mechanism rather than via homogenisation, which is unusual in yeasts [ 68 ]. Yeasts belonging to this clade are ubiquitous on/in fruits, beverages and fruit-based food products (e.g., [ 85 , 95 ]) and were also found in botrytised grapes from the Tokaj region [ 42 , 96 ]. As the fermentation power of Metschnikowia is lower than that observed for other non- Saccharomyces species [ 15 ], the strains found in the Essence wines are not likely to significantly contribute to the fermentation process but they may modulate the composition of the wine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations